Análisis de las propiedades eléctricas de aceites vegetales y minerales utilizados en transformadores de distribución. - Suárez Chamba, Julio Antonio (2020)
The present project was based on the analysis of the electrical properties of mineral oil versus vegetable oil, to identify which oil has a better performance according to its characteristics, evaluating the parameters established in the standards. An overload of 20% was considered in mineral oil transformers according to INEN STANDARD 60076-14; while for transformers with vegetable oil was considered an overload of 168% in rush hours, additionally it has the ability to work 20% continuously overloaded according to the criteria of INEN STANDARD 60076-14. Through the analysis of historical data and laboratory tests, the transformer with vegetable oil was determined in comparison with the mineral oil obtained minor losses and less degradation of isolation in its operating time, once the analysis was carried out a reference area of transformers was determined They are working overloaded, where the transformer with vegetable oil is located can lower the demand with a smaller capacity than mineral oil.